MiR-125b-5p is targeted by curcumin to regulate the cellular antioxidant capacity. (3rd October 2022) - Lin, Lingli; Chen, Xi; Sun, Xiaoting; Xiao, Baoping; Li, Jian; Liu, Jingwen; Li, Guiling
Abstract: As a natural polyphenolic food supplement and the principal curcuminoid in turmeric, curcumin shows antioxidant, anti-inflammatory, and antitumor activities. However, its specific functional mechanism remains unclear. Our preliminary study indicated that miR-125b-5p was downregulated by a curcumin extract. This study aimed to determine whether miR-125b-5p is involved in the antioxidant regulation of curcumin. The results showed that miR-125b-5p overexpression had a pro-oxidant effect by reducing the cellular antioxidant capacity, as well as decreasing the activities of catalase (CAT) and superoxide dismutase (SOD) in the normal liver cell line LO2. However, miR-125b-5p repression significantly increased the cellular antioxidant capacity and enhanced the activities of CAT and SOD. Further investigation demonstrated that the cellular antioxidant capacity induced by curcumin extract was inhibited by miR-125b-5p overexpression. Thus, curcumin may exhibit antioxidant effects by repressing miR-125b-5p expression, which provides new insights into the molecular antioxidant mechanism of curcumin and other functional food components.